Patterns of Transnational Crime in The Border of Sulawesi Sea - Sulu Sea and Threats to Indonesia’s Maritime - Gia Ayu Fita; Andi Ismira; Riady Ibnu Khaldun; Deri Fatra (Resolusi: Jurnal Sosial Politik, 2022)
The rise of transnational crime cases in globalization is fatal if countries with maritime areas do not notice it. It is undoubtedly very influential with the threat to the security of the country's territory. Many transnational crime cases arise in the area between the Sulu Sea and the Sulawesi Sea belonging to Indonesia and the Philippines. The case came from these two countries and other countries both in the Region and those not included in the Southeast Asia Region and has confused the maritime area of the Sulu Sea with the Sulawesi Sea. Not only is the threat coming for the Philippines, but the one that has the most impact is the Indonesian defense area because of the emergence of maritime security threats. So, the concept used to find the many patterns of transnational crime cases has emerged using "maritime security" from Christian Bueger. He explained that the understanding of maritime security is disrupting in terms of defense and terms of economic, political, and geo-strategy. From the analysis and mapping of transnational crime patterns in the Sulu Sea - Sulawesi Sea, it is still a threat to Indonesia's maritime security if Indonesia does not strengthen its defense and minimize transnational criminal activities in the Philippines' border sea area and Indonesia. Literature studies and field research are methods used to analyze maritime security themes.